Holub on Patterns - Holub, Allen (Apress, 2012)
The existing books on design patterns take a catalog approach, where they show the individual design patterns in isolation. This approach is fundamentally flawed, because you can't see how the design patterns actually function in the real world. Most programmers learn by looking at computer programs.